EMG investigation of labial articulations - Uldall, Elizabeth (Annual Report of the Institute of Phonetics University of Copenhagen, 1985)
Results of electromyography with hooked-wire electrodes in one subject in a large number of articulations involving the lips are presented. Stops, pulmonic and glottalic, oral and nasal; fricatives, approximants; rounded vowels; some labials produced by assimilation in English are discussed.